Molecular exercise physiology an introduction - Wackerhage, Henning (London New York Routledge, Taylor & Francis Group, 2014)
"Molecular Exercise Physiology: An Introduction' is the first student-friendly textbook to be published on this key topic in contemporary sport and exercise science. It introduces sport and exercise genetics and the molecular mechanisms by which exercise causes adaptation and various related topics. The text is always linked to real life sport and exercise science situations such as 'what makes people good at distance running?', 'what DNA sequence variations code for a high muscle mass?' or 'by what mechanisms does exercise improve type2 diabetes?"--Provided by publisher.
Introduction to molecular exercise physiology -- Genetics, sport and exercise: background and methods -- Signal transduction and adaptation to exercise: background and methods -- Molecular adaptation to endurance exercise and skeletal muscle fibre plasticity -- Genetics and endurance sports -- Molecular adaptation to resistance exercise -- Genetics, muscle mass and strength -- Molecular sport nutrition -- Human evolution, type 2 diabetes mellitus and exercise -- Molecules, ageing and exercise -- Molecular neuroscience and exercise -- Molecular exercise immunology.
Includes bibliographical references and index.
Keywords: Sports sciences; Sports medicine; Genetics; Sports -- Physiological aspects; Exercise -- Physiological aspects